Gut complex carbohydrates and intestinal microflora in broiler chickens fed with oregano (Origanum vulgare L.) aqueous extract and vitamin E. Issue 4 (23rd August 2016) - Scocco, P.; Forte, C.; Franciosini, M. P.; Mercati, F.; Casagrande‐Proietti, P.; Dall'Aglio, C.; Acuti, G.; Tardella, F. M.; Trabalza‐Marinucci, M.
Summary: One hundred and seventy one‐day‐old female broiler chicks were randomly divided into three groups fed with different dietary treatments: basal control diet (C); C supplemented (2 g/kg) with an oregano aqueous extract (O); C supplemented (150 mg/kg) with vitamin E (E). Growth performance was evaluated at 21 (T1) and 42 days (T2). On the same days, morphological, histochemical and microbiological analyses were performed. The O group showed the highest (p < 0.01) body weight at T1, while no differences were observed at T2. Light microscopic observation and conventional histochemistry showed no differences with regard to the two sampling times, whereas significant differences emerged among the treatments. The O treatment generally enhanced goblet cell reactivity more than both the C and E treatments. Coliform count was lower in the ileum tract of the O group at both T1 and T2 (p < 0.05) and increased with age in all groups. Escherichia coli showed the lowest values in the caecum of the O group (p < 0.001) at both sampling times. Enterococci, lactobacilli and staphylococci populations showed no differences among the different experimental groups in the caecum. In the ileum, the O group did not exhibit the sharp decline (p < 0.001) in the lactic acid bacteria population observed in the other two experimental groups. In conclusion, oregano aqueous extract supplementation seemed to elicit the best response among treatments, enabling better growth performance, enhancing both the quantity and quality of glycoconjugates involved in indirect defence actions and significantly reducing both the coliform and E. coli counts.